The return of depression economics and the crisis of 2008 - Krugman, Paul R. (New York : W.W. Norton, 2009)
Our newest Nobel Prize-winning economist shows how today's crisis parallels the events that caused the Great Depression and explains what it will take to avoid catastrophe.
In his 1999 book, Nobel Prize-winning economist Krugman surveyed the economic crises that had swept across Asia and Latin America, and pointed out that they were a warning: like antibiotic-resistant diseases, the economic maladies that caused the Great Depression were making a comeback. In the years that followed, as Wall Street boomed and wheeler-dealers made vast profits, the crises of the 1990s faded from memory. But when the great housing bubble of the mid-2000s burst, the U.S. financial system proved as vulnerable as those of developing countries. In this greatly updated edition, Krugman shows how the failure of regulation to keep pace with an out-of-control financial system set the United States, and the world, up for the greatest financial crisis since the 1930s. He also lays out the steps that must be taken to contain the crisis, and turn around a world economy sliding into a deep recession.--From publisher description.
'With a new epilogue'--Cover.
Includes index.
Keywords: Recessions -- History -- 21st century; Business cycles -- History -- 21st century; Financial crises -- History -- 21st century; Depressions -- 1929.